2017
DOI: 10.18632/oncotarget.21609
|View full text |Cite
|
Sign up to set email alerts
|

Marital status is associated with superior survival in patients with esophageal cancer: a Surveillance, Epidemiology, and End Results study

Abstract: The impact of marital status on survival among patients with esophageal cancer has not been evaluated in the U.S. population in depth. The aim of the study was to investigate the impact of marital status on survival among patients diagnosed with esophageal cancer. The Surveillance, Epidemiology, and End Results (SEER) database was utilized to identify patients diagnosed with esophageal cancer between 1973 and 2013. Cox regression analysis was performed to evaluate for association between marital status on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
5
23
0
Order By: Relevance
“…A Swedish study demonstrated that unmarried patients diagnosed of gastric cancer or esophageal cancer had poorer survival compared with the married patients 6 . Two recent population-based studies also found that marital status was associated with superior survival in patients with esophageal cancer (EC) 7 - 8 . On the contrary, Brusselaers N et al showed no evidence of a better 5-year survival in married patients with EC who received surgery 9 .…”
Section: Discussionmentioning
confidence: 98%
“…A Swedish study demonstrated that unmarried patients diagnosed of gastric cancer or esophageal cancer had poorer survival compared with the married patients 6 . Two recent population-based studies also found that marital status was associated with superior survival in patients with esophageal cancer (EC) 7 - 8 . On the contrary, Brusselaers N et al showed no evidence of a better 5-year survival in married patients with EC who received surgery 9 .…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we found that single patients tend to have lower risks of developing SPMs (Table 1), which is likely due to the fact that single patients had worse survival outcomes than married patients. [26] For tumor location, the different risks were likely related to different surgical difficulties; for example, upper thoracic esophageal cancer is more difficult to resect than lower esophageal cancer. Currently, there is much controversy related to procedural complexity.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is important to note that the Swedish study only compared patients who had received esophagectomy, whereas the other studies compared all patients with esophageal cancer. [4][5][6] These results may imply that differences in survival between married and unmarried patients may be a result of receipt of treatment. Similarly, studies have found associations between lower use of esophagectomy in Black patients and racial disparities in esophageal cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found associations between marital status and esophageal cancer survival. [4][5][6] Using the SEER database, 2 separate studies found that married patients had higher overall and cancer-specific survival than unmarried patients. 5,6 In contrast, a prospective population-based cohort study from Sweden found no significant differences in 5-year survival between married and unmarried patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation